Pre‐pregnancy weight loss in women with obesity requesting removal of their intra‐uterine contraceptive device in order to conceive: a pilot study of full meal replacement. Issue 4 (11th June 2018) - Brackenridge, L.; Finer, N.; Batterham, R. L.; Pedram, K.; Ding, T.; Stephenson, J.; Barry, J.; Hardiman, P.
Summary: Obesity during pregnancy is associated with increased risks of thromboembolism, gestational diabetes, pre‐eclampsia, miscarriage, congenital anomaly, macrosomia and stillbirth. The current practice, directed at reducing gestational weight gain, is largely ineffective. The present pilot study was designed to assess the acceptability of a 24‐week intensive weight management programme (IWMP; full meal replacement followed by partial meal replacement and weight stabilization) to achieve weight loss for women with obesity requesting removal of their intra‐uterine contraceptive device in order to conceive. Twenty six (65%) of eligible participants consented to the IWMP; three received this as routine National Health Service care in the University College Hospital clinic and 14 participated in the study. The commonest reasons for not participating were dislike of milk, anxiety and lack of support from family and friends. Omitting one woman who dropped out because of problems unrelated to the intervention, the completion rate was 46.2%. Including all women who started the programme, mean body mass index decreased significantly ( P  = 0.005) from 37.8 to 35.3 kg/m 2 . The median percentage decrease was significantly ( P  = 0.007) greater for women who completed the study (14.2) compared to those who dropped out (1.2). These results suggest an impressive level of weight loss in about one third of all women offered the IWMP who had to defer what they were seeking (pregnancy) while following a challenging programme that they were not seeking. However, studies of other interventions, such as partial meal replacement or commercial products, which may have higher rates of completion are still required.